The no people : tribal tales of organizational cliff dwellers - Avolio, Bruce J. (Emerald Publishing Limited : Information Age Publishing, 2011)
This book focuses on capturing one of the most important elements in successful leadership - giving followers a voice and motivating them to use that voice to help the leader be successful. The book is based on taking real stories of effective versus ineffective leaders from around the world, and sharing the lessons learned that facilitate or detract from followers helping leaders to be at their very best. Every leader comes to a cliff, so the author asks the fundamental question, which ones have followers that grab them to pull them back from the abyss, and which ones have followers that give them a nudge towards the abyss?This book threads many of the core concepts associated with the science and practice of leadership, such as authenticity, ownership and innovation, into the stories that help explain how leaders can create the conditions for followers to take ownership in ways that facilitate effective innovation and performance. The stories were purposely chosen for inclusion that would be the ones that readers would most likely identify with and apply to their own development. Moreover, the stories are framed by concepts and constructs in the field of leadership that have been well studied.This is the type of book, that one would expect managers to buy 20 copies for all of their followers to read and then perhaps discuss why the leader wants more "No People" in his or her unit. The book was written to be highly accessible to a very wide range of audiences from teachers to trainers to top management teams. Ideally, keeping the length short, easy to read, and reasonably priced for high volume sales, will offer this book its best chance of success in the global market.